Self-perception of theoretical knowledges and practical skills by primary health care physicians in life-threatening emergencies according to their gender: A cross-sectional study. Issue 8 (26th February 2021) - Cernuda Martínez, José Antonio; Castro Delgado, Rafael; Arcos González, Pedro
Abstract : Abstract: To assess the training received in Emergency Medicine (EM) by the Primary Health Care physicians of Asturias, as well as their perception of their own theoretical knowledge and practical skills in a series of procedures employed in life-threatening emergencies, and also to analyze the differences according to gender. The degree of preparation of Primary Health Care physicians for handling emergencies, according to the gender of the professionals, has never been studied before. Cross-sectional study of a sample of 213 Primary Health Care physicians from the Primary Health Care Service of Asturias, Spain, from among the total of 851 physicians on the staff of the Primary Health Care Service of Asturias. The survey was design ad hoc using the Body of Doctrine of Emergency Medicine proposed by the Spanish Society of Emergency Medicine, which indicates the theoretical and practical procedures that must be mastered by the Primary Health Care physicians. There are nonsignificant differences in the mean of theoretical knowledge and practical skills in many procedures or techniques studied depending on the gender. Female and male Asturian Primary Health Care physicians are generally well prepared to handle life-threatening emergencies. The degree of self-perception and acquisition of general theoretical knowledge and general practical skills for handling life-threatening emergencies is heterogeneous, and differences according to gender are not statistically significant.